A snapshot of the landscape of endometrial cancer in Kenya: Implications of recent updates in pathological classification (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: The incidence of endometrial carcinoma is rising worldwide, partly due to the risingprevalence of obesity. From a diagnostic pathology perspective, it is a heterogeneous disease with avaried range of histomorphological features and is prone to poor interobserver reproducibility. This oftenhas downstream effects on treatment protocols and patient outcomes. The current WHO Classification ofTumors of the Female Genital Tract recommends the incorporation of histology, immunohistochemistry,and molecular testing where possible in the classification of endometrial carcinoma into clinically relevantsubtypes. In Kenya, access to ancillary testing is limited and prohibitively expensive, negatively affectingaccurate tumor classification. In addition, there are limited local data on the various histologic subtypes ofendometrial carcinoma and their respective clinical outcomes.Objectives: To review the classification of endometrial carcinoma as defined by the current WHOClassification contextualized with local clinical, demographic, pathology, and outcome data from twotertiary referral centers in Kenya.Methods: Formalin-fixed paraffin-embedded blocks (FFPE) of 123 cases of endometrial carcinomasbetween 2012 and 2020 were retrieved from the Aga Khan University and Moi Teaching and ReferralHospitals. The clinical history and follow-up data were abstracted. Hematoxylin and eosin sections werereviewed and 11 immunohistochemical markers (MLH1, MSH2, MSH6, PMS2, ER, PR, ARID1A, P16,PTEN, napsin A, and p53) were determined, and analyzed to arrive at a consensus diagnosis.Results: Six endometrial carcinoma subtypes: endometrioid (68 cases, 55%), serous (32 cases, 26%),carcinosarcoma (15 cases, 12%), clear cell (5 cases, 4%), mixed carcinoma (2 cases, 1.5%), anddedifferentiated carcinoma (1 case,